Author Correction: Fundamental investigations on the sodium-ion transport properties of mixed polyanion solid-state battery electrolytes (August, 10.1038/s41467-022-32190-7, 2022) - Deng, Zeyu (NATURE PORTFOLIO, 2023)
10.1038/s41467-022-33224-w